Virtual reality in the rehabilitation of patients with brain stroke sequelae: a bibliographic review (Research, Society and Development, 2020)
Cerebral Vascular Accident (CVA) is a clinical condition that affects the central nervous system (CNS), being classified as hemorrhagic or ischemic, and brings to the affected individual both motor and cognitive deficits. In view of technological advances, rehabilitation has the tendency to rehabilitate through Virtual Reality (VR), performed through exercises based on games, which act in a playful way for functional training and movement facilitation. This study aimed to present the effects of using VR in patients with stroke sequelae, in addition to their concepts and possibilities. This is a literature review, descriptive and exploratory, with a qualitative approach. It used 42 studies extracted from the databases: sciELO, Pubmed, PEDro, Lilacs and Google Scholar. Virtual reality presents significant results as a rehabilitation instrument in the scope of physiotherapy, being considered as a promising area. It is noticed that patients are more interested in this type of treatment. However, further studies should be carried out to improve the evidence on the use of the different technological tools used in the rehabilitation of patients with stroke sequelae.